(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article analyzes some aspects of the formation of aesthetic culture of students, the essence of aesthetic culture and its national identity, the problems of aesthetic culture of students, equipping students with aesthetic knowledge in the system of continuing education, methods and means of developing aesthetic feelings in young people.